2011
DOI: 10.1007/s10495-011-0646-5
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate dehydrogenase requirement for apoptosis induced by aristolochic acid in renal tubular epithelial cells

Abstract: Ingestion of aristolochic acids (AA) contained in herbal remedies results in a renal disease and, frequently, urothelial malignancy. The genotoxicity of AA in renal cells, including mutagenic DNA adduct formation, is well-documented. However, the mechanisms of AA-induced tubular atrophy and renal fibrosis are largely unknown. Epithelial cell death is a critical characteristic of these pathological conditions. To elucidate the mechanisms of AA-induced cytotoxicity, we explored AA-interacting proteins in tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Further, in all treatment groups of our study we found increased levels of two subunits of ATP synthase, whose activation may be a prerequisite for the energy-reliant apoptotic process to proceed [26]. On the other hand, we identified reduced levels of phosphoglycerate kinase 1 (after treatment with all the compounds), voltage-dependent anion-selective protein channel 2 (in K562 cells exposed to IND_S1 , IND_S7 and MEL_S3 ) and glutamate dehydrogenase 1 (in MEL_S3 -treated K562 cells), which have been proposed to act as suppressors of apoptotic phenotypes [27], [28], [29].…”
Section: Discussionmentioning
confidence: 78%
“…Further, in all treatment groups of our study we found increased levels of two subunits of ATP synthase, whose activation may be a prerequisite for the energy-reliant apoptotic process to proceed [26]. On the other hand, we identified reduced levels of phosphoglycerate kinase 1 (after treatment with all the compounds), voltage-dependent anion-selective protein channel 2 (in K562 cells exposed to IND_S1 , IND_S7 and MEL_S3 ) and glutamate dehydrogenase 1 (in MEL_S3 -treated K562 cells), which have been proposed to act as suppressors of apoptotic phenotypes [27], [28], [29].…”
Section: Discussionmentioning
confidence: 78%
“…Apoptosis is considered as the primary mechanism involved in the development of AAN. AA also induces TEC death via apoptosis in acute AAN by targeting the p53 signalling pathway; AA has also been observed to trigger STAT3 dephosphorylation and p53 activation to mediate TEC death via the apoptosis mechanism in acute AAN 60 61 . While AA can influence steroid and lipid metabolism in the liver 58 as it inhibits phospholipase A2, which can form fatty acid and lysophospholipid products by hydrolysing phospholipids 62 .…”
Section: Resultsmentioning
confidence: 99%
“…AA is a natural herbal compound that is toxic to the renal tubulo-interstitial compartment, leading to a rapidly progressive nephropathy, renal failure, and, in some instances, cancer of the urinary tract. AA-induced tubular toxicity involves mitochondrial permeability and injury, leading to defective activation of anti-oxidative enzymes, combined with progressive tubular atrophy, impaired regeneration, and apoptosis/autophagy of proximal tubular epithelial cells (Romanov et al, 2011; Zeng et al, 2014). The anticancer drug doxorubicin (ADR) and its metabolites accumulate in the inner mitochondrial membrane, producing excessive ROS and causing oxidative damage.…”
Section: Discussionmentioning
confidence: 99%